Out of the Penkelemes: The ECOWAS project as transformation - Abdourahmane Idrissa (University of Oxford, Global Economic Governance Programme (GEG), 2013)
This paper uses the case of the Economic Community of West African States (ECOWAS) to argue (1) that "development as liberalization" effectively sustains poverty and economic decline or stagnation in the types of countries that make up the membership of that community, and (2) that regionalism may be a source of alternative, more helpful policy. Despite continuous reformatory thrust, the "development as liberalization" strategy has so far failed to alter the unfair social contracts of West African states, essentially because that would entail altering the international economic system into which those social contracts are ultimately anchored, an impossible proposition. Taking stock of this, I examine the ECOWAS project in light of the alternative solutions that it potentially harbors, especially as it promotes "economic transformation", in addition to "development as liberalization". The key question for the future of ECOWAS, I will eventually argue, lies in the way in which it will either create a productive compatibility between these two options, or at least prevent the now dominant one from smothering the one which I claim is more promising.
Keywords: 330